Pharmaceutical protein production by yeast: Towards production of human blood proteins by microbial fermentation - Martínez, J.; Liu, Lifang; Petranovic, D.; Nielsen, J. (2012)
Since the approval of recombinant insulin from Escherichia coli for its clinical use in the early 1980s, the amount of recombinant pharmaceutical proteins obtained by microbial fermentations has significantly increased. The recent advances in genomics together with high throughput analysis techniques (the so-called - omics approaches) and integrative approaches (systems biology) allow the development of novel microbial cell factories as valuable platforms for large scale production of therapeutic proteins. This review summarizes the main achievements and the current situation in the field of recombinant therapeutics using yeast Saccharomyces cerevisiae as a model platform, and discusses the future potential of this platform for production of blood proteins and substitutes. © 2012 Elsevier Ltd.